(untitled) (Marketing Journal, 2025)
This study analyzes the integration of artificial intelligence (AI) technologies in global tourism and hospitality and evaluates their applicability in Uzbekistan. Based on bibliometric review, case study analysis, SWOT assessment, and secondary statistica l data, the current state of digitalization is examined. Findings indicate that AI can enhance revenue, customer satisfaction, and energy efficiency. Strategic recommendations are proposed at government, business, and academic levels. The research presents a practical roadmap for developing smart tourism in Uzbekistan.